2019
DOI: 10.1007/978-3-030-27920-2_12
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Properties in the Diet of Tibetan Macaques at Mt. Huangshan: A Case for Self-Medication

Abstract: Life history strategies include growth, maintenance, and reproduction (Gadgil and Bossert 1970), all of which are dependent upon a proper diet for metabolic functions. Animal feeding strategies are based on finding and consuming a balance of the most essential nutritional elements, carbohydrates, fats, proteins, trace elements, and vitamins, while at the same time avoiding the negative impacts of secondary metabolites in plants (Lambert 2011; Simpson et al. 2004). These secondary metabolites protect plants fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…For example, in ruminants, individuals consuming a diet high in plant fiber were found to exhibit higher gut fungal diversity compared with individuals fed a diet lower in plant fiber, such grains (Denman and Mcsweeney, 2006;Denman et al, 2010;Boots et al, 2013). Although, we do not have quantitative data on the fiber content of the wild plant foods consumed by the wild and semi-provisioned macaques, they naturally consume a broad-based diet that included grasses, leaves, fruits, and insects (Huffman et al, 2020). However, the main diet of captive group was corn supplemented with sweet potatoes.…”
Section: Discussionmentioning
confidence: 96%
“…For example, in ruminants, individuals consuming a diet high in plant fiber were found to exhibit higher gut fungal diversity compared with individuals fed a diet lower in plant fiber, such grains (Denman and Mcsweeney, 2006;Denman et al, 2010;Boots et al, 2013). Although, we do not have quantitative data on the fiber content of the wild plant foods consumed by the wild and semi-provisioned macaques, they naturally consume a broad-based diet that included grasses, leaves, fruits, and insects (Huffman et al, 2020). However, the main diet of captive group was corn supplemented with sweet potatoes.…”
Section: Discussionmentioning
confidence: 96%
“…Most species of the genera Cladosporium were reported as plant endophytic pathogens ( Venkateswarulu et al, 2018 ). As Tibetan macaques are highly dependent on plants for food ( Huffman et al, 2020 ), the plant-associated fungi may partly colonize their guts. However, it is difficult to identify if these core fungi, shared by gut and plant, are symbionts, transient inhabitants or passengers from the available data.…”
Section: Discussionmentioning
confidence: 99%
“…Tree species information is presented in Supplementary Table 2 . We selected these specific tree species because their leaves are consumed with a total relative frequency of 52% ( Huffman et al, 2020 ). We obtained 14 topsoil samples from MH and 17 from MT.…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly relevant for human evolution since humans and non-human primates share a common evolutionary history and have a similar physiology and it is possible that they share ways to combat diseases through medicinal plant use (Huffman 2016 ). This includes studies of chimpanzees ( Pan troglodytes ) and gorillas ( Gorilla gorilla ) (Basabose 2002 ; Cousins and Huffman 2002 ; Rogers et al 2004 ; Huffman 2001 , 2003 , 2015 ; Huffman and Seifu 1989 ; Huffman et al 1996 ; Mclennan and Huffman 2012 ; Krief et al 2006 ; Masi et al 2012 ), Japanese macaques ( Macaca fuscata ) (Huffman et al 2010 ; Tasdemir et al 2020 ), sifakas ( Propithecus verreauxi verreauxi ) (Carrai et al 2003 ), lemurs ( Eulemur rufifrons ) (Peckre et al 2018 ), Tibetan macaques ( Macaca thibetana ) (Huffman et al 2020 ), and orangutans ( Pongo pygmaeus ) (Morrogh-Bernard et al 2017 ). Some of these studies have demonstrated both health maintenance and deliberate self-medication that is processed using a combination of innate mechanisms, individual learning, and cultural transmission (Huffman 2016 ).…”
Section: Evolutionary Contextmentioning
confidence: 99%
“…In all recorded cases, the plants used have been subjected to pharmacological analyses that have identified specific properties that correspond with the use of the plant. In addition to the use of plants in treatment, there are many examples of the use of food-medicines, or medicinal foods, plants that are eaten as food, but that also contain important medicinal properties and therefore provide an underlying protection, with specific food items added in particular, in relation to parasite infection and reproductive events, though Huffman et al ( 2020 ) have identified the use of Epimedium davidii Franch, Berberidaceae, potentially as a means of stress reduction in a preliminary study on Tibetan macaques. Icariin ( 10 ), a major prenylated flavonol glycoside, is the active principle associated with stress reduction and anti-depressant properties via downregulation of glucocorticoid receptor activity and regulation of hippocampal neuroinflammation (Li et al 2015 ).…”
Section: Evolutionary Contextmentioning
confidence: 99%